HUBUNGAN KECERDASAN EMOSIONAL DENGAN MOTIVASI BELAJAR IPS TERPADU SISWA SMP NEGERI 2 AMANDRAYA - Baziduhu Laia (Institut Pendidikan Tapanuli Selatan, 2021)
This study aims: 1) To describe the level of emotional intelligence of students. 2) To describe the level of student motivation. 3) To see the relationship between emotional intelligence and learning motivation of class students. This research uses correlational quantitative research. The population and sample of the study were all students of class VIII who may be 50 people. Based on the research results, it is obtained 1) The overall level of intelligence is in the medium category. 2) The total level of student motivation to learn is in the medium category. 3) the relationship between emotional intelligence and student learning motivation is H0 rejected and Ha accepted. It can be perfected that students with high emotional intelligence will also have higher levels of student motivation. The level of emotional intelligence of students, the level of student learning motivation is also getting lower. Based on this research, the researchers suggest that social studies teachers be more intensive in providing intelligence to increase students' intelligence and learning motivation in schools.